An innovative framework for encouraging future thinking in ESD: A case study in a French school. (August 2018) - Julien, Marie-Pierre; Chalmeau, Raphaël; Vergnolle Mainar, Christine; Léna, Jean-Yves
Highlights: The French education for sustainable development circulars offers possibilities to project into the future. The French curricula offer a limited and segmented place for the future. An innovative educational framework that helps pupils to think the future of their territory. Future thinking is a fundamental skill in education for sustainable development. The future thinking ability can be defined as a meta-competence that encompasses many of the key skills in education for sustainable development. Abstract: Although imagining the future is a key skill requirement in education for sustainable development (ESD), it is rarely taught. The French Education Ministry recently included the future in its ESD circulars and geography curriculum. We therefore developed an innovative framework for thinking about the future, featuring several different learning tools. This paper describes how schoolchildren aged 8–12 years imagined the future of the area where they live in an interdisciplinary context (Human‐Environment Observatory) in the course of a 3-year experiment. Our framework allowed them to work on different dimensions of the future and imagine several possible futures. We discuss the need for pupils to handle complexity and uncertainty when working with the future. The ability to project themselves into the future enables pupils/citizens to make sound choices and to form opinions by comparing their own views with those of others.